Experiential learning methods for biostatistics students: A model for embedding student interns in academic health centers. Issue 1 (25th December 2022) - Pomann, Gina‐Maria; Boulware, L. Ebony; Chan, Cliburn; Grambow, Steven C.; Hanlon, Alexandra L.; Neely, Megan L.; Peskoe, Sarah B.; Samsa, Greg; Troy, Jesse D.; Yang, Lexie Zidanyue; Thomas, Samantha M.
Abstract: This manuscript describes an experiential learning program for future collaborative biostatisticians (CBs) developed within an academic medical program. The program is a collaborative effort between the Biostatistics, Epidemiology, and Research Design (BERD) Methods Core and the Master of Biostatistics (MB) programme, both housed in the Department of Biostatistics and Bioinformatics at Duke University School of Medicine and supported in partnership with the Duke Clinical and Translational Science Institute. To date, the BERD Core Training and Internship Program (BCTIP) has formally trained over 80 students to work on collaborative teams that are integrated throughout the Duke School of Medicine. This manuscript focuses on the setting for the training program, the experiential learning model on which it is based, the structure of the program, and lessons learned to date.